Management of endometriomas - S O Dubrovina; Yu D Berlim; V S Gimbut; L V Krasilnikova; K A Areshyan (IP Berlin A.V., 2017)
Ovarian endometriomas could affect up to 44% of women with endometriosis, and are often associated with pelvic pain and infertility. Treatment options include expectant management, medical and/or surgical treatment, and in vitro fertilization. The choice of treatment depends mostly on the associated symptoms. In most cases, surgery is the preferred choice, since endometriomas do not respond to medical treatment, which may only treat associated pain. In case of infertility, in vitro fertilization and embryo transfer may be a suitable alternative to surgery, particularly when there is no associated pain. According to the best available scientific evidence, laparoscopic excision of the endometrioma wall should be considered the procedure of choice. The surgical excision may damage the ovarian reserve. At the same time, recent evidences demonstrate that part of the damage may be due to the presence of the endometrioma itself. Indication to surgical treatment should balance the possible risks of damaging the ovarian reserve with the advantages of surgery in terms of satisfactory pain relief rates and pregnancy rates, and of obtaining tissue specimen for ruling out the rare cases of unexpected ovarian malignancy. A score system to guide the clinician in the decision to perform or withhold surgery and endometriosis fertility index are presented.